Characterization of Coal Quality Based On Ash Content From M2 Coal-Seam Group, Muara Enim Formation, South Sumatra Basin - Nasution, Frillia Putri; Nalendra, Stevanus (UIR PRESS, 2017)
Muara Enim Formation is well known as coal-bearing formation in South Sumatra Basin. As coal-bearing formation, this formation was subjects of many integrated study. Muara Enim Formation can be divided into four coal-seam group, M1, M2, M3, and M4. The M2 group comprising of Petai (C), Suban (B), Lower Mangus (A2), and Upper Mangus (A1). Depositional environments of Group M2 is transitional lower delta plain with sub-depositional are crevasse splay and distributary channel. The differentiation of both sub-depositional environments can be caused the quality of coal deposit. One of quality aspects is ash content. This research conducted hopefully can give better understanding of relationship between depositional environments to ash content. Group M2 on research area were found only Seam C, Seam B, and Seam A2, that has distribution from north to central so long as 1400 m. Coal-seam thickness C ranged between 3.25-9.25 m, Seam B range 7.54-13.43 m, and Seam C range 1.53-8.37 m, where all of coal-seams thickening on the central part and thinning-splitting to northern part and southern part. The ash content is formed from burning coal residue material. Ash contents on coal seam caused by organic and inorganic compound which resulted from mixing modified material on surrounded when transportation, sedimentation, and coalification process. There are 27 sample, consists of 9 sample from Seam C, 8 sample from Seam B, and 10 sample from Seam A2. Space grid of sampling is 100-150 m. Ash content influenced by many factors, but in research area, main factor is existence of inorganic parting. Average ash content of Seam C is 6,04%, Seam B is 5,05%, and Seam A2 is 3,8%. Low ash content influenced by settle environment with minor detrital material. High ash content caused by oxidation and erosional process when coalification process. Ash content on coal in research area originated from detritus material carried by channel system into brackish area or originated from higher plant in brackish area. The high ash content also can be caused by after the coal deposited. It had originated from overburden horizon which infill in cleat of coal seam.